(3GfOeGL GdTQcGJ GdeSGgeI GdYGeI h GdBKGQ GdbGfhfjI GdeJQJHI YdjgG (B/s - (3HUHhU, aGjR GSeGYjds ((3YeGf(B: s (3OGQ GdKbGaI(B, s, 2010)
(3eGgjI GdGfOeGL , CKQ GdGfOeGL Ydi GdTQcGJ h Ydi Mbhb GdeSGgejf , BKGQ GdGfOeGL Ydi Mbhb OGFfj h eOjfj GdTQcGJ GdOGNdI ajg , BKGQ GdGfOeGL Ydi MedI CSfGO GdbQV h Ydi CUMGH MUU GdJCSjS , h Ydi YbhO GdTQcI GdefOeLIs
(3eQGLY U(B.249s
Keywords: (3GdTQcGJ GdYGeIs; (3GdTQcGJ GdeSGgeIs; (3GdbGfhf GdJLGQjs; (3GdeSGgehfs